2019
DOI: 10.7150/thno.36585
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of the alternative splicing landscape in head and neck squamous cell carcinoma reveals novel events associated with tumorigenesis and the immune microenvironment

Abstract: Alternative splicing (AS) has emerged as a key event in tumor development and microenvironment formation. However, comprehensive analysis of AS and its clinical significance in head and neck squamous cell carcinoma (HNSC) is urgently required. Methods: Genome-wide profiling of AS events using RNA-Seq data from The Cancer Genome Atlas (TCGA) program was performed in a cohort of 464 patients with HNSC. Cancer-associated AS events (CASEs) were identified between paired HNSC and adjacent normal tissues and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 73 publications
5
67
0
Order By: Relevance
“…Some of these variants could even become novel antigens for specific targeted therapy of HNSCC, such as the splicing variant of GSN, which was reported to be able to serve as a biomarker of HNSCC and a neoantigen for HNSCC treatment ( 18 ). In addition, HNSCC is characterized by clinical heterogeneity ( 19 ). For instance, patients with recurrent and/or metastatic HSNCC can be treated with cetuximab, an anti-EGFR antibody, but only ~13% of patients with metastasis respond to this therapy ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these variants could even become novel antigens for specific targeted therapy of HNSCC, such as the splicing variant of GSN, which was reported to be able to serve as a biomarker of HNSCC and a neoantigen for HNSCC treatment ( 18 ). In addition, HNSCC is characterized by clinical heterogeneity ( 19 ). For instance, patients with recurrent and/or metastatic HSNCC can be treated with cetuximab, an anti-EGFR antibody, but only ~13% of patients with metastasis respond to this therapy ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study aimed at identifying AS events (ASE) in human papillomavirus (HPV)-negative HNSCC demonstrated that the analysis of ASE in HPVnegative HNSCC identified multiple changes that may be associated with carcinogenesis, including carcinogenic DOCK5 variants (52). A recent study conducting a genome-wide analysis of AS events using RNA-seq data from the TCGA program in a sample of 464 HNSC patients revealed new AS events associated with carcinogenesis and the immune microenvironment (55). Likewise, another study systematically analyzed the RNA binding protein (RBP) gene mutations, copy number, and gene expression pattern, and changes of AS in these tumors, and AS sequence enrichment and the motif of the change in cancer RBP expression (56).…”
Section: Discussionmentioning
confidence: 99%
“…Although the identification, screening and clinical use of neoantigens still face various challenges, neoantigens with tumor tissue specificity and high immunogenicity are expected to benefit more patients as potential targets for cellular immunotherapy [31,32]. Previously, TCGA as the principal guide to understanding of the complex tumor biology [33], large-scale sequencing data were used to identify prognostic AS events and revealed pathogenesis through regulatory splicing networks in colorectal cancer and head-neck carcinoma [34,35]. More and more AS-related prognostic models have been established, showing excellent efficacy in various cancers.…”
Section: Discussionmentioning
confidence: 99%